Análise dos determinantes para a captação de recursos pelas empresas de base tecnológica vinculadas às incubadoras de empresas mineiras - Walison Librelon de Oliveira (2021)
Investment in Technology-Based Companies (TBF) is a vital activity for the diffusion of technological innovation, however of extreme complexity with several uncertainties. TBF has characteristics that tend to alienate investors, who are not willing to take the associated risks. In this way, grant resources are essential to the development of the innovation ecosystem. Associated with this scenario, Brazil is still far below the main global players, when compared to investments in Research and Development (R&D), which in 2018 reached only 1.3% of GDP. This framework is aggravated by the inefficiency in making innovation efforts more effective, with Brazil in the 62nd position in the innovation ranking, among 131 economies, in 2020. Considering the importance of TBF for innovation and technological development, this study aimed to analyze which determinants can influence fundraising by, linked to business incubators, in the State of Minas Gerais. Determinants are understood as the variables that may or may not explain the ability to obtain resources, such as launching innovative products, age and TBF billing, number of graduate students from the incubator anchor universities, GDP of the municipalities that houses the companies, total resources raised by the incubators, among others. This work is of an empirical and exploratory nature, where descriptive statistical and regression analyzes were performed for panel data, in order to understand the dependence relationships between the determining variables and the fundraising by the TBF. To carry out this study, data from InovaData-MG was used, which is a platform for monitoring and monitoring technological parks and business incubators in Minas Gerais. It was considered as a sample of the research universe a total of 383 TBF, linked to incubators of mining companies, which responded to surveys on the Platform, in the periods from 2009 to 2018. The results showed that the variables age and earnings of TBF, municipal GDP per capita, as well as the resources that the anchor incubator received throughout its trajectory are not significant for the TBF to have a greater chance of raising funds. On the other hand, the number of graduate students linked to the Higher Education Institutions (HEI) anchors, and the number of innovative products launched on the market positively affect the chances of raising funds by TBF.